CONTENT ANALYSIS OF EDUCATIONAL COMIC STRIPS ABOUT SOCIO-SCIENTIFIC ISSUES: A CASE IN NORTH KALIMANTAN, INDONESIA - Abrori, Fadhlan Muchlas; Lavicza, Zsolt; Saimon, Musa (Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to investigate fifteen comic strips due to training activities conducted in North Kalimantan. The investigation was carried out through content analysis based on comic formats and socio-scientific issues in comic strips. The fifteen comics analysed are based on the comic format, which refers to the single gag or continuous strip style. Meanwhile, topics are grouped based on science disciplines. The findings imply that teachers prefer to develop single gag style comics rather than continuous strips. For topics, the majority of teachers prefer issues related to environmental science.